2002
DOI: 10.1046/j.1529-8817.2002.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

DIEL VARIATIONS IN OPTICAL PROPERTIES OF MICROMONAS PUSILLA (PRASINOPHYCEAE)1

Abstract: Micromonas pusilla (Butcher) Manton et Parke, a marine prasinophyte, was used to investigate how cell growth and division affect optical properties of phytoplankton over the light:dark cycle. Measurements were made of cell size and concentration, attenuation and absorption coefficients, flow cytometric forward and side light scattering and chl fluorescence, and chl and carbon content. The refractive index was derived from observations and Mie scattering theory. Diel variations occurred, with cells increasing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
90
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 46 publications
15
90
0
Order By: Relevance
“…From this figure it is evident that the model ascribes the observed increase in c p during the illuminated part of the day to an increase in cellular scattering, rather than cell abundance (compare Fig. 6a and b), as suggested by previous studies (e.g., Stramski et al, 1995;DuRand et al, 2002). The c p dynamics at night are instead related to both variations in cell abundance and scattering cross-section (Fig.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…From this figure it is evident that the model ascribes the observed increase in c p during the illuminated part of the day to an increase in cellular scattering, rather than cell abundance (compare Fig. 6a and b), as suggested by previous studies (e.g., Stramski et al, 1995;DuRand et al, 2002). The c p dynamics at night are instead related to both variations in cell abundance and scattering cross-section (Fig.…”
Section: Resultssupporting
confidence: 63%
“…Two field studies showed that ξ decreased during the day and increased at night suggesting that the relative size of the particles affecting c p increased during the day and decreased at night (Oubelkheir and Sciandra, 2008;Slade et al, 2010). Laboratory studies have also shown diel variability in ξ (Claustre et al, 2002;DuRand et al, 2002;Stramski and Reynolds, 1993;Stramski et al, 1995), but only DuRand et al (2002) clearly reported that the spectral slope of the scattering coefficient decreased during the day and increased at night as recently observed in the field.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Carbon (pg C cell Bertilsson et al 2003, Heldal et al 2003, and Verity et al 1992 Values taken or calculated from Johnson et al 2009, Durand et al 2002, and Montagnes et al 1994 Values taken or calculated from Waite et al 1997 andMontagnes et al 1994. Table 2 for references.…”
Section: Speciesmentioning
confidence: 99%
“…Previously published data on maxima and minima in either cell volume or carbon quota during cell divisions of nanophytoplankton were obtained from the following sources: Eppley & Coatsworth (1966), Kohata & Watanabe (1986, Berdalet et al (1992), DuRand & Olson (1998), Varela & Harrison (1999), DuRand et al (2002, and Ohi et al (2002Ohi et al ( , 2003. From these sources, we selected the data giving both the cell volume and carbon quota during cell division: Kohata & Watanabe (1989), DuRand & Olson (1998), Varela & Harrison (1999) and DuRand et al (2002).…”
Section: Published Datamentioning
confidence: 99%